The Usage of Adverbial Connectors by Saudi Female EFL Learners - AlShlowi, Arwa Hamdan (Journal of English Language Teaching and Applied Linguistics, 2023)
The paper investigates the different usage of adverbial connectors in Saudi Female EFL learners’ (NNS) writings compared to native English (NS) writings. The 10 most frequent connectors in the two corpora, a compiled Saudi English learners’ corpus and the BNC Baby Corpus of academic prose were selected to examine the differences between both writing samples. The results support previous studies that Saudi learners are generally more prone to overuse and underuse connectors and tend to overuse specific listing and contrastive connectors while ignoring others redundantly. It also presents evidence of Saudi learners’ tendency to position adverbial connectors only sentence-initial or sentence medial, whereas native speakers of English interchange between medial and initial positions. These findings should be considered pedagogically to enhance EFL learners’ understanding of English discourse connectors to produce better cohesive writing.